The Students' Reflective Thinking Processes Analysis in Solving PISA Math Problems on Quantity Content - Pasaribu, Rita Rupiani; Sujadi, Imam; Indriati, Diari (Universitas Sebelas Maret, 2023)
The skills that students should have and develop are the ability to evaluate results and reflective thinking based on their learning experiences. The reflective thinking is crucial for students to recognize what is expected during the learning process. Therefore, this research aims to analyze students' reflective thinking processes in solving PISA math problems on quantity content and the reflective thinking involves three stages, namely: 1) Reacting 2) Elaborating, and 3) Contemplating. This study employed a qualitative approach with a case study design. This research was conducted at SMP N 1 Tanon, Sragen, with the research subjects, six students from VII-A Class. Think Aloud and interviews were applied as data collection techniques. Think-aloud was selected because it aids students in observing, identifying, and measuring the content of students' thoughts during the problem-solving process. The PISA questions used included three types of mathematical processes, namely: 1) formulating 2) employing, and 3) interpreting. The results of the analysis obtained: 1) Formulating question types, 5 subjects can meet all the stages of reflective thinking; 2) Employing question type, 2 subjects can meet all the stages of reflective thinking; 3) Type of Interpreting questions, 3 subjects can reach all the stages of reflective thinking.Keywords: Reflective Thinking, PISA, Quantity